Canadian Critical Luxury Studies Decentring Luxury (Bristol Intellect, 2022)
luxury; Canadian fashion; Montreal; Indigenous; production; fashion; history; colonialism; canada; luxury studies; community; consumption
English
Keywords: Canada; Cultural studies; Fashion and textile design; Media studies; The Arts; "luxury; Canadian fashion; Montreal; Indigenous; production; fashion; history; colonialism; canada; luxury studies; community; consumption"